The Feasibility of Enzyme Immunoassay Tests in the Absence of a Conventional Source of Electricity - Camille, S.U. DOSSOU; Oswald, Y. DJIHINTO; Roland, E.V. SAGBO; Azanmanvo, M. YEDJENOU; Magloire, Da Silva; Honoré, S. BANKOLE (Journal of Biotechnology and Biomedical Science, 2020)
Background of the Study African  countries are facing frequent blackout. Thus in sub Saharan region, due to frequent power cut, the laboratory professionals find sometimes difficulty to carry out earlier diverse diagnostic tests. Objective The  aim of this work is to evaluate the feasibility of enzyme immunoassay tests in the absence of a conventional source of electricity. Methods We  developed a battery-powered experimental device, which was then applied to diagnose measles. The samples included 45 sera randomly selected from non-haemolysed serum samples received and stored at the National Public Health Laboratory of Benin. The experimental device is composed of two devices (Devices 1 and 2). The Device 1 provided an average temperature of 34.47 °C, 20 min after starting. With Device 2 an average temperature of 20.32 °C is obtained 15 min after starting. Results With  the experimental device the same rate of measles antibody-positive sera (44.68%) was obtained as recorded from the test using the standard equipment of laboratory. The experimental device detected 18 negative and 8 intermediate results against respectively 19 and 7 by the standard equipment. The analysis of the results of both equipments shows a concordance rate of 93.33% with a kappa reproducibility coefficient of 0.89. Conclusion The  device conceived in our study is a simply equipment allowing the realization of the enzyme immunoassay tests, in this case the ELISA anti-measles test. The rate of concordance obtained shows that this device can be used with commercial kits and at temperatures close to those recommended by the manufacturer without altering the results.
Keywords: power cut; experimental device; enzyme immunoassay test; measles.